PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA INDUSTRI OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2015 - Mega Kartika Purnama Sari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims at determining the effect of cash turnover, receivables turnover, and inventory turnover on the profitability of automotive industry listed in the Indonesia Stock Exchange in the years of 2010-2015. The independent variables of this study are cash turnover, receivables turnover, and inventory turnover. The dependent variable of this study is company’s profitability measured using Return On Assets (ROA). This quantitative research is an explanatory research. From a population of 5 automotive industries, all of them were selected as the sample through non-probability sampling technique. This study uses secondary data, which were analyzed using multiple linear regression. The result of this research shows that the influence of cash turnover is insignificantly positive on company’s profitability. Receivables turnover negatively and significantly influence company’s profitability, but inventory turnover positively and significantly influence company’s profitability. Cash turnover, receivables turnover, and inventory turnover simultaneously have positif and significant influence on company’s profitability. Receivables turnover is the most dominant variable on company’s profitability.Keyword : Cash Turnover, Receivables Turnover, Inventory Turnover, Profitability, Return On Assets.